Pengaruh Model Pembelajaran Pendidikan Matematika Realistik Indonesia (PMRI) berbantuan LKS Etnomatematika terhadap Kemampuan Literasi Numerasi Ditinjau dari Minat Belajar Siswa - Nurul Aini Adiningsih; Fadhilah Rahmawati; Aprilia Nurul Chasanah (MaPan : Jurnal Matematika dan Pembelajaran, 2023)
Numerical literacy ability is an important ability that students must have. This study aims to analyze the impact of the Indonesian Realistic Mathematics Education learning model (PMRI) using ethnomathematics worksheet media on students' numeracy literacy skills related to students' learning interests. This research is quantitative research with a quasi-experimental design. The samples in this study were students of class VIII D and VIII F SMP Negeri 6 Magelang who were selected through cluster random sampling technique. In this study, the instrument used was numeracy literacy tests and student learning interest questionnaires. Based on data analysis calculations, the results show that: (1) The numeracy literacy skills of students who take PMRI learning assisted by ethnomathematics worksheets are better than students who take PMRI learning; (2) Students with high learning interest have better numeracy skills than students with moderate learning interest, students with moderate learning interest have the same good numeracy literacy skills as students who have low learning interest, and students with high learning interest have the ability better numeracy literacy than students with low interest in learning; (3) There is no interaction between the learning model and learning interest on students' numeracy literacy skills.